The BMP homolog Gbb provides a retrograde signal that regulates synaptic growth at the Drosophila neuromuscular junction. - McCabe, B.D.; Marques, G.; Haghighi, A.P.; Fetter, R.D.; Crotty, M.L.; Haerry, T.E.; Goodman, C.S.; O'Connor, M.B. (Neuron, 2003)
We show that the BMP ortholog Gbb can signal by a retrograde mechanism to regulate synapse growth of the Drosophila neuromuscular junction (NMJ). gbb mutants have a reduced NMJ synapse size, decreased neurotransmitter release, and aberrant presynaptic ultrastructure. These defects are similar to those we observe in mutants of BMP receptors and Smad transcription factors. However, whereas these BMP receptors and signaling components are required in the presynaptic motoneuron, Gbb expression is required in large part in postsynaptic muscles; gbb expression in muscle rescues key aspects of the gbb mutant phenotype. Consistent with this notion, we find that blocking retrograde axonal transport by overexpression of dominant-negative p150/Glued in neurons inhibits BMP signaling in motoneurons. These experiments reveal that a muscle-derived BMP retrograde signal participates in coordinating neuromuscular synapse development and growth.